2017
DOI: 10.1016/j.stemcr.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

RBP4-STRA6 Pathway Drives Cancer Stem Cell Maintenance and Mediates High-Fat Diet-Induced Colon Carcinogenesis

Abstract: SummaryThe transmembrane protein, STRA6, functions as a vitamin A transporter and a cytokine receptor when activated by vitamin A-bound serum retinol binding protein 4 (RBP4). STRA6 activation transduces a JAK2-STAT3 signaling cascade and promotes tumorigenesis in a xenograft mouse model of colon cancer. We show here that RBP4 and STRA6 expression is associated with poor oncologic prognosis. Downregulating STRA6 or RBP4 in colon cancer cells decreased the fraction of cancer stem cells and their sphere and tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 48 publications
3
65
1
Order By: Relevance
“…This observation correlates with epidemiological studies showing that different types of diets modulate the risk to develop intestinal cancers [11,12], with high fat containing diets leading to higher prevalence for the development of colon cancers [13,14]. Here, deregulated stem cell activities appear to be directly associated with alterations in intestinal JAK/STAT signaling [15].…”
Section: Introductionsupporting
confidence: 84%
“…This observation correlates with epidemiological studies showing that different types of diets modulate the risk to develop intestinal cancers [11,12], with high fat containing diets leading to higher prevalence for the development of colon cancers [13,14]. Here, deregulated stem cell activities appear to be directly associated with alterations in intestinal JAK/STAT signaling [15].…”
Section: Introductionsupporting
confidence: 84%
“…317,318 Moreover, studies have also found aberrant activation of STATs in human cancers, such as head and neck cancer, 319 endometrial cancer, 320 breast cancer, diffuse large B cell lymphoma, 321 HCC, 322 colorectal cancer, glioma, 323 and colon cancer. 324 Furthermore, aberrant STAT5 signaling has been found in the pathogenesis of hematologic and solid organ malignancies. 325,326 The JAK/STAT pathway is evolutionarily conserved.…”
Section: Major Signaling Pathways In Cscsmentioning
confidence: 99%
“…There is growing evidence associating colon cancer development with environmental causes, such as a high-fat diet [6]. Pro-obesity diets enhance the numbers and function of the Lgr5 + stem cells and/or colon tumorigenesis by activating multiple pathways, including peroxisome proliferator-activated receptor delta (PPAR-δ) and Wnt/β-catenin signatures [7], retinol binding protein 4 (RBP4)-stimulated by the retinoic acid 6 (STRA6) pathway [8], and fatty acid oxidation [9]. Similar changes were observed when dietary constituents, such as palmitic acid and oleic acid (OA), were administered, suggesting a critical role for fatty acid in the maintenance of colon CSCs.…”
Section: Introductionmentioning
confidence: 99%